Utilization of Merdeka Mengajar Platform by Productive Mathematics Teachers : Impacts, Motivations, and Strategies - Ikram, Fadhil Zil; Anaguna, Nursyam; Rosidah, Rosidah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the impact, motivation, and strategy of using the Merdeka Mengajar platform by productive mathematics teachers. This study used mixed-method with case studies in its qualitative research and quasi-experiments in its quantitative research. The participants of the case study were 15 productive mathematics teachers, and the sample of the quasi-experiment was one of the classes taught by the teacher. Quantitative data were obtained from students’ learning outcomes, and qualitative data from semi-structured teacher interviews. The quantitative analyses used were descriptive statistics and inferential statistics. The qualitative analysis refers to three steps: data condensation, data display, and decision-making. The results showed that the impact obtained by mathematics teachers was an enhancement in competence and knowledge, including those related to teaching and technology. Learning innovations inspired by learning outcomes in PMM were effectively implemented in the mathematics classroom. What motivates teachers to optimize the use of PMM varies from the desire to continue learning and provide the best quality of learning to the desire to contribute to student success and to be role models. There are three elements in productive mathematics teachers’ strategies to optimize the use of PMM in self-development. They are targets, consistency, notes and implementation with feedback, and self-reward as a supporting element.